Perception of Pegasus in Rwanda: A Dive into Privacy Concerns - Nkurunziza Egide (International Journal of Human Computing Studies, 2023)
This study explores the perceptions, fears, and nuanced opinions of Rwandans regarding the presence and potential misuse of Pegasus spyware, a globally controversial surveillance tool. Utilizing a mixed-method approach, we conducted a comprehensive survey involving 1,000 respondents, both within Rwanda and in diaspora, representing diverse age groups and genders. The research findings reveal a pervasive awareness of Pegasus among the respondents, with 80% expressing strong concerns about its potential misuse for surveillance. Moreover, a substantial 95% of respondents believe that the Rwandan government either currently uses or has previously employed Pegasus for surveillance purposes, while 70% assert that its deployment in Rwanda raises significant worries about privacy and individual rights. Notably, 80% of respondents associate the presence of Pegasus with a negative impact on freedom of speech and expression. Drawing from these findings, our study recommends a multifaceted approach, including stringent regulatory measures, technical safeguards, and an informed public discourse on surveillance technologies. It emphasizes the need for collaborative efforts involving governments, the private sector, and citizens to ensure the responsible and ethical deployment of surveillance tools like Pegasus, extending beyond Rwanda's borders to address global concerns. This research contributes to the ongoing global conversation about the delicate balance between national security imperatives and the preservation of individual privacy in the age of advancing digital surveillance technologies.